2006
DOI: 10.2337/dc06-0254
|View full text |Cite
|
Sign up to set email alerts
|

Chromium Picolinate Supplementation Attenuates Body Weight Gain and Increases Insulin Sensitivity in Subjects With Type 2 Diabetes

Abstract: OBJECTIVE -Chromium picolinate (CrPic) supplementation has been suggested to improve glycemia, but there are conflicting reports on efficacy. We sought to determine the effect of CrPic on insulin sensitivity, glycemic control, and body composition in subjects with type 2 diabetes.RESEARCH DESIGN AND METHODS -Thirty-seven subjects with type 2 diabetes were evaluated. After baseline, subjects were placed on a sulfonylurea (glipizide gastrointestinal therapeutic system 5 mg/day) with placebo for 3 months. Subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
153
1
7

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(172 citation statements)
references
References 38 publications
11
153
1
7
Order By: Relevance
“…Anderson et al (14) revealed that chromium ingestion in both short (2 months) and longer (4 months) terms displays beneficial effects on plasma glucose, insulin, and hemoglobin A 1c concentrations. In another study, Cr(pic) 3 supplementation significantly improved insulin sensitivity and glucose control and attenuated BW gain and visceral fat in type 2 diabetic patients taking sulfonylurea (38). Further study is warranted to scrutinize the longitudinal effect of chromium treatment in diabetes, obesity, and insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anderson et al (14) revealed that chromium ingestion in both short (2 months) and longer (4 months) terms displays beneficial effects on plasma glucose, insulin, and hemoglobin A 1c concentrations. In another study, Cr(pic) 3 supplementation significantly improved insulin sensitivity and glucose control and attenuated BW gain and visceral fat in type 2 diabetic patients taking sulfonylurea (38). Further study is warranted to scrutinize the longitudinal effect of chromium treatment in diabetes, obesity, and insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Patients receiving total parenteral nutrition devoid of chromium display signs of insulin resistance, which can be reversed by chromium supplementation, suggesting the role of chromium as an essential trace metal for carbohydrate and lipid metabolism (36). Further experimental and clinical studies have consolidated the efficacy of chromium in the management of type 2 diabetes and associated comorbidities such as insulin resistance and obesity (37,38). In a recent clinical trial, effects of chromium on cardiac function were assessed in diabetic patients with a focus on Q-T interval prolongation, a parameter associated with high fasting glucose levels, high plasma insulin levels, and increased fasting C-peptide levels in diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…22 Cefalu et al (2010) 23 Chen et al (2014) 24 Crawford et al (1999) 25 Evans (1989) 26 Ghosh et al (2002) 27 Gunton et al (2005) 28 Grant and McMullen. (1982) 29 Grant et al (1997) 30 Hermann et al (1998) 31 Hermann et al (1994) 32 Jain et al (2012) 40 Lee and Reasner (1994) 41 Li et al (1992) 42 Li (1994) 43 45 Martinez et al (1985) 46 Mossop (1983) 47 Offenbacher and Pi-Sunyer (1980) 48 Offenbacher et al (1985) 49 Pasman et al (1997) 50 Pei et al (2006) 51 Rabinovitz et al (1983) 52 Rabinovitz et al (2004) 53 Racek et al (2006) 54 Riales et al (1981) 55 Singer and Geohas (2006) 56 Sharma et al (2011) 57 Sherman et al (1968) 58 Thomas and Gropper (1996) 59 Urberg and Zemel (1987) 60 …”
Section: Studies Measuring Hba1cmentioning
confidence: 99%
“…Baseline HbA1c levels were 8.2%, and these fell to 7.6 % post treatment; however, mean standard deviations or mean standard errors were not reported, nor were final HbA1c values reported in the control group, precluding statistical analysis. Martin et al 45 enrolled 17 T2DM patients whose FPG values were >125 mg/dL and <170 mg/dL at baseline and who were also taking hypoglycemic medications (sulfonylureas). Patients received chromium picolinate 1000 lg/d for 24 weeks in a double-blind RCT using a per-protocol analysis.…”
Section: Studies Measuring Hba1cmentioning
confidence: 99%
“…Chromium supplementation can be beneficial for fasting serum glucose, total cholesterol and triglyceride concentrations and the percentage of HbA1c, as well as body weight and insulin sensitivity in T2DM patients [18][19][20]. On the other hand, it was not possible to evaluate chromium intake from the participants' diets, so it is unknown whether there was any necessity to supplement their diets with this trace mineral.…”
Section: Discussionmentioning
confidence: 99%